Bankruptcy Analysis Using the Springate and Grover Methods at PT. Bank Danamon Indonesia Tbk - Nurirna Sakinah; Alwi; Nurhayati (Pustaka Digital Indonesia, 2025)
The development of the economy is inseparable from the role of financial institutions, particularly banks, which play a significant part in shaping monetary policies, foreign exchange supervision, and securities registration. PT Bank Danamon Indonesia Tbk, as one of the largest private banks in Indonesia, has faced declining financial performance over the past five years (2019-2023), marked by increasing debt and decreasing net profit. This study aims to analyze the bankruptcy potential of PT Bank Danamon Indonesia Tbk using the Springate and Grover methods, which are bankruptcy prediction models based on financial ratio analysis. The results of this analysis are expected to provide valuable information for stakeholders in making decisions related to the company’s financial health. This research also compares its findings with previous studies that utilized the Altman Z-score model, thus offering a comprehensive overview of liquidation risk and the bankruptcy potential of PT Bank Danamon Indonesia Tbk.